Mythic lizard rediscovered: redescription of Anolis laevis Cope 1876 (Squamata: Anolidae) from recent collections in Peru - Ayala-Varela, Fernando; Venegas, Pablo J.; García-Ayachi, Luis Alberto; Poe, Steven (Zootaxa, 2026)
Anolis laevis Cope 1876, a poorly known South American anole characterized by an unusual rudimentary rostral appendage, had not been observed since its original description 150 years ago. Here, we report the rediscovery of A. laevis within approximately 50 to 100 km of its type locality in eastern Peru, including two adult males and, for the first time, adult females. Morphological analyses confirm pronounced sexual dimorphism, with females lacking the proboscis. This trait parallels the condition seen in other species of Anolis with a proboscis and may represent evolutionary convergence of the appendage in different lineages. We provide a detailed redescription of A. laevis, highlighting diagnostic morphological traits that distinguish it from other proboscid and morphologically similar South American Anolis species. Unusual traits of A. laevis include large head scales including few loreal rows, a distinct dorsal crest, presence of a dewlap in both sexes, and sexually dimorphic dewlap coloration. Our findings contribute to clarifying the taxonomy and morphological variation of poorly known anoles.